Financial Knowledge, Financial Attitude, Self-Efficacy, Mathematical Anxiety and Financial Literacy - Latifah Putranti; Putri Sriariani Tabun (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2024)
Financial literacy is knowledge, skills, and beliefs that influence attitudes and behaviors to improve the quality of decision-making and financial management that not only knows and understands financial institutions but also community behavior that can be changed and enhanced regarding financial products and services. Financial literacy is needed to manage financial resources to achieve financial well-being successfully. This study aims to determine financial knowledge, attitudes, self-efficacy, and mathematical anxiety towards financial literacy. This study uses a quantitative method. The Population in this study consisted of all students in the Special Region of Yogyakarta. A sample of 100 respondents was selected based on specific criteria. The data collection technique for this study used a questionnaire. The study's results showed that financial knowledge, financial attitudes, and self-efficacy influenced financial literacy, while mathematical anxiety did not affect financial literacy.